Effect of Repeated Injection of Iodixanol on Renal Function in Healthy Wistar Rats Using Functional MRI. (4th April 2018) - Wang, Yongfang; Ren, Ke; Xie, Lizhi; Sun, Wenge; Liu, Yi; Li, Songbai
Abstract : Purpose . To determine the optimal time interval of repeated intravenous injections of iodixanol in rat model and to identify the injury location and causes of renal damage in vivo . Materials and Methods . Rats were randomly divided into Control group, Group 1 with one iodixanol injection, and Group 2 with two iodixanol injections. Group 2 was subdivided into 3 cohorts according to the interval between the first and second iodixanol injections as 1, 3, and 5 days, respectively. Blood oxygen level-dependent (BOLD) imaging and diffusion weighted imaging (DWI) were performed at 1 hour, 1 day, 3 days, 5 days, and 10 days after the application of solutions. Results . Compared with Group 1 (7.2%), Group 2 produced a remarkableR 2 ⁎ increment at the inner stripe of the renal outer medulla by 15.37% (P = 0.012 ), 14.83% (P = 0.046 ), and 13.53% (P > 0.05 ), respectively, at 1 hour after repeated injection of iodixanol. The severity of BOLD MRI to detect renal hypoxia was consistent with the expression of HIF-1 α andR 2 ⁎ was well correlated with HIF-1 α expression (r = 0.704 ). The acute tubular injury was associated with urinary NGAL and increased significantly at 1 day. Conclusions . Repetitive injection of iodixanol within a short time window can induce acute kidney injury, the impact of which on renal damage in rats disappears gradually 3–5 days after the injections.